Role of previous infection with SARS-CoV-2 in protecting against omicron reinfections and severe complications of COVID-19 compared to pre-omicron variants: a systematic review - Maryam Arabi (3927509) (2023)
Background The SARS-CoV-2 virus elicited a major public concern worldwide since December 2019 due to the high number of infections and deaths caused by COVID-19. The Omicron variant was detected in October 2021 which evolved from the wild-type SARS-CoV-2 and was found to possess many mutations. Omicron exhibited high transmissibility and immune evasion as well as reduced severity when compared to the earlier variants. Although vaccinated individuals were largely protected against infections in previous waves, the high prevalence of both reinfections and breakthrough infections with Omicron was observed. The aim of this review is to understand the effectiveness of previous infection on subsequent reinfection, given its significance in driving public health policy, including vaccination prioritization and lockdown requirements. Methods A comprehensive literature search was conducted using several databases to target studies reporting data related to the effectiveness of the previous infection with SARS-CoV-2 in protecting against the Omicron variant. Screening of the studies, quality assessment and data extraction were conducted by two reviewers for each study. Results Only 27 studies met our inclusion criteria. It was observed that previous infection was less effective in preventing reinfections with the Omicron variant compared to the Delta variant irrespective of vaccination status. Furthermore, being fully vaccinated with a booster dose provided additional protection from the Omicron variant. Additionally, most infections caused by Omicron were asymptomatic or mild and rarely resulted in hospitalizations or death in comparison to the Delta wave. Conclusion A majority of the studies reached a consensus that although previous infection provides some degree of immunity against Omicron reinfection, it is much lower in comparison to Delta. Full vaccination with two doses was more protective against Delta than Omicron. Receiving a booster dose provided additional protection against Omicron. It is therefore clear that neither vaccination nor previous infection alone provide optimal protection; hybrid immunity has shown the best results in terms of protecting against either Omicron or Delta variants. However, additional research is needed to quantify how long immunity from vaccination versus previous infection lasts and whether individuals will benefit from variant-specific vaccinations to enhance protection from infection. Other Information Published in: BMC Infectious Diseases License: https://creativecommons.org/licenses/by/4.0 See article on publisher's website: https://dx.doi.org/10.1186/s12879-023-08328-3